(3GdebGQHI GdfXQjI ddEfJGLjI GdcdjI dYhGed GdEfJGL hGdCLhQ (B/s - (3ROhf, LeGds ((3GdLRGFQ(B: s (3OGQ CLjGd GdQbej (B, s, 2023)
(3jSYi gPG GdcJGH GdYdej Edi eYGdLI hJhVjM CMO Cge GdbVGjG GdJj JhGLggG GdMcheGJ ShGA Ydi eSJhi GdGbJUGO Gdcdj Ch GdGbJUGO GdLRFj GdeJeKdI aj GdQaY ef eSJhjGJ GdGfJGLjI GdcdjI dYhGed GdGfJGL Ydi GdeSJhi Gdcdj hGdLRFj eY GdMaGX Ydi eSJhjGJ ebHhdI ef GdCLhQ JVef bOQI TQGFjI LjOI ddYeGd hGdehXajf, hYdjg aEf gPG GdcJGH JVef CQHYI aUhd NGUI HGdEfJGLjI GdcdjI dYhGed GdEfJGL, MjK Je JNUjU GdaUd GdChd Edi cd eG jJYdb HGdeaGgje GdfXQjI, GeG GdaUd GdKGfj abefG ajg HJhVjM CSGdjH bjGSgG hcaUd KGdK MGhdfG EHQGR Cge GdeMOOGJ dgG hGdYhGed GdeDKQI YdjgG, haj GdaUd GdQGHY Je JfGhd WQb hCSGdjH JMSjfgG, ceG Je JNUjU CQHYI aUhd CNQi eJYdbI HGdCLhQ, MjK Je JNUjU GdaUd GdNGeS ddebGQHI GdfXQjI ddCLhQ CeG GdaUd GdSGOS aJe ajg JaUjd CZdH fXQjGJg, hcaUd SGHY CHQRfG eYXe eMOOGJ GdCLhQ (B((3GdeMOOGJ GdGbJUGOjI, Shb GdYed(B)(3, hGNjQG haj GdaUd GdKGef CVafG eMOOGJ CNQi ddCLhQ cGdGSJKeGQ aj QCS GdeGd GdHTQj hGdbOQI GdTQGFjI EVGaI Edi JhVjM GdYdGbI GdJHGOdjI Hjf GdGfJGLjI GdcdjI dYhGed GdEfJGL hGdCLhQ(B.s
(3HHdjhZQGajG(B: (3U U(B.239-258s
Keywords: (3GdCLhQs; (3GdGfJGLs; (3GdJfejI GdGbJUGOjIs